Short term deuterium depletion in drinking water reduced tumor induced oxidative stress in mice liver - YARAT, AYŞEN (My University, 2022)
© 2022The aim of current work was able to show the oxidant effect of cancer cells found in any part of the body on the liver and to investigate the possible protective effect of deuterium-depleted water (DDW) on this oxidant effect by determining of some liver parameters. Ehrlich ascites tumor bearing BALB/c mice were used for this purpose. BALB/c mice were selected randomly and divided into four groups (n = 5 in each group) as control group, tumor group, control+DDW group, tumor+DDW group, fifteen days after tumor cell injection, liver tissue samples were taken for all groups. In the tumor group, liver lipid peroxidation, sialic acid and protein carbonyl levels, xanthine oxidase, myeloperoxidase, catalase, gamma-glutamyl transferase, sorbitol dehydrogenase, glutathione peroxidase and glutathione reductase activities, were significantly higher than those in the control group while glutathione levels and paraoxonase1, sodium potassium ATPase, glutathione-S-transferase, alanine transaminase and aspartate transaminase activities decreased significantly. Compared with the tumor group, the changes in all parameters except sialic acid, catalase, alanine transaminase and aspartate transaminase were reversed in the DDW given tumor groups, while sialic acid and catalase values continued to increase, and alanine transaminase and aspartate transaminase values continued to decrease. In conclusion, the consumption of DDW may be beneficial and protective against excessive oxidative stress in cancer complications.
Keywords: Tıp; Histoloji-Embriyoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Histology and Embryology; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Yaşam Bilimleri (LIFE); Biyoloji ve Biyokimya; PATOLOJİ; HÜCRE BİYOLOJİSİ; Life Sciences (LIFE); BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; PATHOLOGY; CELL BIOLOGY; Patoloji ve Adli Tıp; Hücre Biyolojisi; Pathology and Forensic Medicine; Cell Biology; Antioxidants-oxidant; Deuterium-depleted water; Ehrlich ascites tumor; Enzyme; Liver; Oxidative stress